Improvement of Mahārat al-Kalām in Arabic Learning through Total Physical Response Method - Nurul Musyafaah; Nilna Indriana; Rizka Widayanti; Muhammad Afthon Ulin Nuha (Al-Ma‘rifah: Jurnal Budaya, Bahasa, dan Sastra Arab, 2023)
The Total Physical Response (TPR) learning method was developed by James J. Asher. He argues that direct pronunciation to children or students contains an order, and then children or students will respond physically before producing verbal or speech responses. The aims of this study were (1) to find out how far speaking skills (mahārat al-kalām) in Arabic have increased through the TPR method in MTsN 4 Jombang, and (2) to find out the supporting and inhibiting factors in increasing mahārat al-kalām through the TPR method in MTsN 4 Jombang. This research method uses a descriptive-qualitative approach with data collection techniques using observation, interviews, documentation, and oral tests. The data analysis technique uses data condensation, data display, and conclusion drawing or verification. The results showed that (1) with the TPR learning method, the final test score of Arabic learning for mahārat al-kalām in cycle 1 was 74.3% (good). After being given referrals again in cycle 2, it reached 87.6% (very good); (2) The supporting factors that influence speaking activities are language (linguistics) and non-linguistics, while the inhibiting factors are more dominant due to a lack of vocabulary (mufradāt) mastery.